Work-Life Balance sebagai Prediktor Kinerja Guru Sekolah Dasar di Kecamatan Tenayan Raya, Pekanbaru - Abida, Puja Sabil; Noviana, Eddy; Jais, Muhammad (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: Work-life balance has become an important factor influencing teachers’ professional performance, as teachers are required to manage various responsibilities in both professional and personal domains. Elementary school teachers face multiple demands, including teaching activities, administrative responsibilities, student guidance, and social roles within the community. Therefore, maintaining a balance between work and personal life is essential to support effective teacher performance. This study aims to analyze the level of work-life balance, the level of teacher performance, and the effect of work-life balance on the performance of elementary school teachers in Tenayan Raya District, Pekanbaru. This study employed a quantitative approach using a survey method. The research sample consisted of 96 elementary school teachers selected through a total sampling technique. Data were collected using a Likert-scale questionnaire based on work-life balance indicators developed by Fisher et al. and teacher performance indicators proposed by Supardi. The data were analyzed using descriptive statistics and simple linear regression analysis with the assistance of SPSS version 24. The results showed that the levels of work-life balance and teacher performance were categorized as moderate. The regression analysis revealed that work-life balance had a positive and significant effect on teacher performance, as indicated by a significance value of 0.000 (<0.05). These findings indicate that better work-life balance contributes to improved teacher performance in carrying out professional responsibilities. This study highlights the importance of institutional support and teacher welfare policies that promote a healthy balance between professional demands and personal life as part of efforts to improve the quality of elementary education. Abstrak: Keseimbangan antara kehidupan kerja dan kehidupan pribadi (work-life balance) menjadi salah satu faktor penting yang dapat memengaruhi keberhasilan guru dalam menjalankan tugas profesionalnya. Guru sekolah dasar menghadapi berbagai tuntutan, seperti pelaksanaan pembelajaran, administrasi pendidikan, serta peran sosial di lingkungan sekolah dan masyarakat, sehingga kemampuan mengelola keseimbangan peran menjadi aspek penting dalam mendukung kinerja. Penelitian ini bertujuan untuk menganalisis tingkat work-life balance, tingkat kinerja guru, serta pengaruh work-life balance terhadap kinerja guru sekolah dasar di Kecamatan Tenayan Raya, Pekanbaru. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Sampel penelitian terdiri atas 96 guru sekolah dasar yang ditentukan menggunakan teknik total sampling. Pengumpulan data dilakukan melalui kuesioner dengan skala Likert, sedangkan analisis data menggunakan statistik deskriptif dan regresi linear sederhana dengan bantuan SPSS versi 24. Hasil penelitian menunjukkan bahwa tingkat work-life balance dan kinerja guru berada pada kategori sedang. Hasil analisis regresi menunjukkan bahwa work-life balance berpengaruh positif dan signifikan terhadap kinerja guru dengan nilai signifikansi 0,000 (<0,05). Temuan ini menunjukkan bahwa peningkatan keseimbangan antara tuntutan pekerjaan dan kehidupan pribadi dapat mendukung peningkatan kinerja guru dalam melaksanakan tugas pembelajaran. Penelitian ini memberikan implikasi bahwa penguatan kebijakan kesejahteraan guru dan penciptaan lingkungan kerja yang mendukung keseimbangan kehidupan kerja perlu menjadi bagian dari strategi peningkatan mutu pendidikan dasar.